Acculturations in Intercultural Marriage Families: The Story from Denpasar City - Jayantini, I Gusti Agung Sri Rwa; Sulatra, I Komang; Andriyani, Anak Agung Ayu DIan; Sharita, Jasmine (Humanus, 2022)
Acculturation in families with parents having different cultures is a fascinating phenomenon. It is a worth investigating issue to be seen from type of intercultural marriage the family chooses and how children adapt to their parents’ different backgrounds.  This study aims at analyzing types of intercultural marriage taking place in Denpasar, the capital city of Bali province, Indonesia and investigating how the children from these families face the acculturation process. Twenty children in Denpasar city, Bali experiencing intercultural marriage were involved in the research. They were observed and interviewed to identify how acculturation takes place in their family. The study reveals that in the sense of acculturation as a process of adjustment and adaptation, it occurs in four types of intercultural marriage, namely (1) submission/immersion (being submitted to one), (2) obliteration (adopting new language and culture), (3) compromise (maintenance with limitations), and (4) consensus (full maintenance). Each type of intercultural marriage is supportively adopted in the families that give the opportunity for the children to live harmoniously despite the different backgrounds and cultures their parents have.